Probing the thermal stability and the decomposition mechanism of a magnesium–fullerene polymer via X-ray Raman spectroscopy, X-ray diffraction and molecular dynamics simulations. Issue 7 (28th January 2016) - Aramini, Matteo; Niskanen, Johannes; Cavallari, Chiara; Pontiroli, Daniele; Musazay, Abdurrahman; Krisch, Michael; Hakala, Mikko; Huotari, Simo
Abstract : The dynamic decomposition mechanism was established in an element-specific way for a magnesium-intercalated fullerene polymer. Abstract : We report the microscopic view of the thermal structural stability of the magnesium intercalated fullerene polymer Mg2 C60 . With the application of X-ray Raman spectroscopy and X-ray diffraction, we study in detail the decomposition pathways of the polymer system upon annealing at temperatures between 300 and 700 °C. We show that there are at least two energy scales involved in the decomposition reaction. Intermolecular carbon bonds, which are responsible for the formation of a 2D fullerene polymer, are broken with a relatively modest thermal energy, while the long-range order of the original polymer remains intact. With an increased thermal energy, the crystal structure in turn is found to undergo a transition to a novel intercalated cubic phase that is stable up to the highest temperature studied here. The local structure surrounding magnesium ions gets severely modified close to, possibly at, the phase transition. We used density functional theory based calculations to study the thermodynamic and kinetic aspects of the collapse of the fullerene network, and to explain the intermediate steps as well as the reaction pathways in the break-up of this peculiar C60 intermolecular bonding architecture.